The SAC-1 Integer Arithmetic System-Version III - Collins, George E. (University of Wisconsin-Madison Department of Computer Sciences, 1973)
This report documents a new version of the SAC-1 Integer Arithmetic System, a system for performing arithmetic operations and input-output on infinite-precision integers. The new version contains improved algorithms for base conversion and some new subprograms. However, the most important improvement is the documentation provided by this report, which includes, for each subprogram, a functional specification, a semi-formal algorithm description, both theoretical and empirical computing times, and an ANSI standard Fortran program listing which corresponds closely to the algorithm description.